Are Artificial Sweeteners a Healthier Alternative to Sugar? - Julia Buszek; Piotr Czerniak; Adrianna Antoszewska; Weronika Bargiel; Dominika Bąk; Halszka Wajdowicz; Mateusz Warzocha; Michał Medygrał; Sylwia Buszek; Aldona Sokołowska; Maciej Rumian; Alicja Kosel (Quality in Sport)
Introduction